Fire Resistance Test of Geopolymer Coatings on Non-Metallic Underlying Substrates - Mamoń, Filip; Jaskevič, Martin; Mareš, Jakub; Novotný, Jan (Manufacturing Technology Journal, 2023)
This article summarizes the results from the fire resistance test of geopolymer suspensions in the form of coatings on non-metallic substrates. Their heat resistance was evaluated based on the burn-through time compared to the uncoated substrate. Non-metallic substrate materials, extruded polystyrene (XPS) and chipboard (DTD) were chosen as the underlying substrates for GP suspension research. Parameters from the fire resistance test as fire test duration of geopolymer coatings and percentage increase in burn time of geopolymer coatings on an XPS and DTD substrates compared to an uncoated substrate were evaluated. One of the discussed point was also the addition of CaCO3 and Al(OH)3 for studding flame retardancy effect.
Keywords: geopolymer; coatings; fire resistance test; non-metallic substrate; flame retardancy